A model of asynchronous bi-hemispheric production in global agricultural commodity markets - Miranda, Mario J.; Glauber, Joseph W. (Agricultural and Applied Economics Association, 2022)
The past forty years have witnessed a rapid expansion of grain and oilseed production in the southern hemisphere, particularly in South America. The growth of southern hemisphere production is significant, not only because it has increased supplies to meet growing world food needs but also because it has effectively shortened the global crop growing cycle from twelve months to six months. In this paper, we develop and analyze a semi‐annual stochastic spatial–temporal equilibrium model of a generic agricultural market with two major exporting regions, North and South, which plant and harvest at different times of the year. As a case study, we calibrate our model parameters to reflect the stylized facts of the global soybean market between 1980 and 2019, with the United States serving as North and Brazil and Argentina serving as South. We find that more balanced production, with both hemispheres producing nearly equal amounts at different times of the year, has, from a global perspective, shortened the traditional crop “season” from twelve months to six months, allowing semi‐annual adjustments to planned production that stabilize supply and prices in all regions while reducing global inventories.